Peningkatan Kapabilitas Business Plan, Network, dan Marketing Guna Akselerasi Bisnis UMKM Sekolah Wirausaha Aisyiyah - Zulkifli Nurul Haqq; Annisa Fajri (UNIB Press, 2023)
The development of the business world is currently experiencing significant developments. Massive digitalization is spreading in all aspects of human life, making the expertise to use a qualified digital device a must. With the emergence of new entrepreneurs, it is hoped that it will have a direct impact on improving people's welfare as well as accelerating economic progress and equity, increasing Indonesia's competitiveness through superior-based products and creative industries so as to create new jobs, as well as absorbing a large domestic market. on local products. In line with this, the community service collaboration team of the Management Study Program, Faculty of Economics, Universitas Muhammadiyah Semarang and Sekolah Wirausaha ‘Aisyiyah.